PENGUTAN KAPASITAS RELAWAN PMI MELALUI PELATIHAN PERAWATAN KELUARGA DAN PRAKTIK LAPANGAN PADA PANTI JOMPO - ., mugiyanto; Hadi, Syaikhul; Yuli Astuti, Anna Kartika; Hastuti, Diah (LPPM POLBITRADA, 2026)
The capacity building program for Indonesian Red Cross Volunteers through integrated family care training with field practice is crucial. The background of this activity is based on the increasing need for elderly health services that require the support of skilled caregivers, while the capacity of volunteers to provide basic assistance in family care is still limited. Therefore, the role of Indonesian Red Cross Volunteers as Cargivers is very important in the quality of life of the elderly, especially in improving physical and psychosocial needs, especially in conditions of dementia. (Syifak, S et al., 2022). The implementation method includes the preparation stage, training (delivery of family care and basic assistance materials), and direct practice in nursing homes. Evaluation was carried out using a pre-test and post-test approach as well as observation of participant skills during field practice. Practice-based training was chosen because it has been proven effective in improving the competence and confidence of caregivers in providing care (Amin Y, et al. 2025). The results of the activity show how the knowledge and skills of volunteers in carrying out basic assistance and elderly care have increased. Field practice provides real experience that strengthens participants' application skills in real situations. Thus, this activity is effective in increasing the capacity of PMI volunteers in family care. Similar programs need to be developed sustainably to improve the quality of community-based healthcare services, particularly for the elderly.